ROLE AND DYNAMICS OF INTRATELLURIC FLUID IN LIQUID-IMMISCIBILITY SEPARATION OF BASALTIC MAGMA - Prokoptsev B.G. (My University, 1989)
We have shown that the conditions of extrusion of deep-sea lavas on the sea floor are such that the makeup of their quenched flows preserves some structural characteristics of their endogene state and of the processes taking place in the basaltic magma. One of the disputed problems of petrogenesis still involves such processes as liquid-immiscibility separation and subsequent fluid-magma differentiation, which our data indicate are general links in the chain of igneous evolution. We assume that the structure of the microveinlets, and also that of their centers and the channels joining them, represent the structure and the corresponding model of the mechanism of separation of intratelluric fluid from the magmatic melt. It is also evident that this process is related to the development of the final stage of liquid-immiscibility of the magma and is probably one aspect of the complex process of fluid-magma differentiation of a melt.